2020
DOI: 10.21203/rs.3.rs-59409/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial Profile and Their Antibiotic Resistance Pattern Among HIV Patients Diagnosed with Pneumonia in Felege-Hiwot Referral Hospital, Bahir Dar, Northwest Ethiopia

Abstract: Background: Bacterial pneumonia remains the major cause of morbidity and admissiondiagnosis among human immunodeficiency virus infected individuals. In the study area, data about the bacterial profile of pneumonia and their antimicrobial resistance pattern among people living with human immunodeficiency virus is limited. Hence, this study was aimed to estimate the prevalence of bacterial pneumonia, antibiotic resistance patterns of isolated bacteria and associated factors among HIV patients in Felege Hiwot Ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…All of them are cross-sectional in study design and were published between 2000 and October 2022. Among those studies four were done in Amhara region (Dessie (18), Gondar (16), Bahir Dar (15,22)), two studies in SNNP (Arbaminch (23) and Hawassa ( 17)) and the rest three studies were independently reported from Addis Ababa (24), Oromia (25) and Tigray regional state (26). Seven of the included studies were done among all adult CAP patients whereas the rest two were done among adult CAP patients living with HIV/AIDS (Table 1 and Supporting le 4:-Table S3) Table 1 Characteristics of studies done on CAP among adult patients in Ethiopia in the year between 2000 and October 2022.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All of them are cross-sectional in study design and were published between 2000 and October 2022. Among those studies four were done in Amhara region (Dessie (18), Gondar (16), Bahir Dar (15,22)), two studies in SNNP (Arbaminch (23) and Hawassa ( 17)) and the rest three studies were independently reported from Addis Ababa (24), Oromia (25) and Tigray regional state (26). Seven of the included studies were done among all adult CAP patients whereas the rest two were done among adult CAP patients living with HIV/AIDS (Table 1 and Supporting le 4:-Table S3) Table 1 Characteristics of studies done on CAP among adult patients in Ethiopia in the year between 2000 and October 2022.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In the present study, the predominant isolate was S. pneumoniae 49 (26.3%) followed by K. pneumoniae 46 (47.4%) and P. aeruginosa 34 (19.4%). This result is inconsistent with other studies conducted in Ethiopia such as Arbaminch, 38 Jimma, 43 Bahirdar, 44 others with different geographical regions of the world like India, 1 , 46 United Kingdom 40 and Spain 15 showed that S. pneumoniae was the predominant isolate On the contrary, previous studies conducted in Mekelle, 21 Addis Ababa 41 Tanzania 45 and Bahirdar 47 ; and elsewhere in the world including Nepal, 17 Nigeria 43 , 44 and India. 14 , 26 , 48 This dominance could be attributed to their capsular nature and the emergence of strains from both species with additional genetic traits.…”
Section: Discussionmentioning
confidence: 65%
“…A study done by Genetu et al in Ethiopia in 2019 reported Klebsiella pneumoniae (29.7%) and Staphylococcus aureus (25%) [ 21 ] as the most prevalent isolates while a study done by Mihret et al also from Ethiopia in 2021 isolated Streptococcus pneumoniae (28%), Klebsiella pneumonia (26.3%) and Pseudomonas euroginosa (19.4%) [ 22 ]. Our study isolated Moraxella species (27.4%), Streptococcus pneumoniae (25.4%), Haemophilus influenza (22.4%).…”
Section: Discussionmentioning
confidence: 99%